Effects of landscape heterogeneity on the elevated trace metal concentrations in agricultural soils at multiple scales in the Pearl River Delta, South China. (November 2015) - Li, Cheng; Li, Fangbai; Wu, Zhifeng; Cheng, Jiong
Abstract: Based on multiple geo-accumulation indices and correlation and partial redundancy analyses, we examined the spatial patterns of agricultural soil contaminations for As, Pb, Cd, Cr, and Ni in the Pearl River Delta, South China and their relations with landscape heterogeneity at small, medium and large spatial scales. We found that the concentrations of trace elements were slightly elevated, and most trace metals had a geogenic origin. Landscape variables explained 21–53% of the variation of elevated trace metal concentrations with an increasing explanatory power from the small to the large scale. The three variable groups representing parent materials, distance density characteristics and land use had different contributions to the elevated trace metals among scales. Both the distance density variables and land use pattern had a stronger influences on trace metal concentrations at a small scale than at a larger scale, while the parent materials was important at all the scales. Highlights: The correlations of soil pollutants and landscape patterns were scale-dependent. The primary sources of elevated trace metal contents were of geogenic origin. The impacts of land use on soil trace metals decreased with the scale studied. Abstract : Landscape variables can be used as proxies of soil trace metal pollutants at multiple scales.